2001
DOI: 10.1111/j.1834-7819.2001.tb00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of periodontal conditions among public‐funded dental patients in Australia

Abstract: Background: The aims of this study were to describe periodontal health status by gender, type of care, geographic location and age and to investigate associations of these factors with tooth loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
1
12
0
2
Order By: Relevance
“…While the longitudinal and intergenerational findings are unique, the DMHDS cross-sectional and descriptive findings are reasonably consistent with the limited data available from other studies (Brennan et al 2001, Oral Health U.S. 2002, Slade et al 2007). This is true also of the findings for the parents at the age-32 assessment (Slade et al 2007).…”
Section: Discussionsupporting
confidence: 85%
“…While the longitudinal and intergenerational findings are unique, the DMHDS cross-sectional and descriptive findings are reasonably consistent with the limited data available from other studies (Brennan et al 2001, Oral Health U.S. 2002, Slade et al 2007). This is true also of the findings for the parents at the age-32 assessment (Slade et al 2007).…”
Section: Discussionsupporting
confidence: 85%
“…1). In the final screen, 24 studies were excluded (interreviewer agreement κ = 0.96) by full‐text evaluation and are described in Box 1 18‐41 …”
Section: Resultsmentioning
confidence: 99%
“…4 The population monitoring and surveillance activity of the Australian Institute of Health and Welfare's Dental Statistics and Research Unit (DSRU) has revealed persistent and significant differences between population groups in adult oral health in Australia for more than a decade, showing that adults who were economically disadvantaged experienced poorer oral health 5 as did Indigenous Australians, 6 older adults in residential care, 7 migrants, 8 rural and remote dwellers, 9 and adults eligible for publicly funded dental care. [10][11][12][13] The linkage by DSRU of 1987/88 National Oral Health Survey data to area indices of socioeconomic status revealed marked inequality in the rates of edentulism and in the prevalence of decayed, missing and filled teeth. 5 Other research found an eightfold difference in the percentage of adults aged 45-64 years who reported edentulism (complete tooth loss) across f ive levels of household income.…”
Section: S Ocial Inequality In Population Oralmentioning
confidence: 99%